Victim-Centered Justice Revisited: Rebalancing Power in the Restorative Justice System - Iwan Sumiarsa; Yasmirah Mandasari Saragih; Tuti Widyaningrum; Wagiman (Magister Ilmu Hukum Fakultas Hukum Universitas Riau, 2026)
The contemporary criminal justice system continues to marginalize victims by prioritizing state authority and a perpetrator-centric paradigm, although restorative justice is increasingly prominent as a victim-centered alternative. This condition reveals a persistent gap between the normative promise of restorative justice and its practical realization. This study examines how victim-centered justice is conceptualized and implemented in the restorative justice system, with particular attention to the role of power relations. Using conceptual and theoretical legal research approaches, this study applies critical and system-oriented analysis to examine restorative justice as a normative and institutional framework. These findings suggest that the main limitation of restorative justice stems not from the absence of victim participation, but from the structural conditions that limit such participation. Legal subordination, institutional marginality, symbolic inclusion, and unaddressed power asymmetry systematically limit agency and victim's influence over outcomes. As a result, restorative justice often reproduces existing inequalities rather than redressing them. This study offers a new reconceptualization of victim-centered justice by positioning the rebalancing of power as a fundamental principle of the restorative justice system. The contribution advances a power-sensitive theoretical framework and provides practical insights for strengthening the agency, legitimacy, and substantive justice of victims in restorative practice.